Neural network controller based sequential switch cascaded H-bridge multilevel inverter - Ramya, M; Usha Rani, P; Ganesan Subramanian, G; Ramash Kumar, K (International Journal of Engineering and Technology, 2018)
This paper presents a novel cascaded multilevel inverter structure with reduced devices. This structure is termed as sequential switch cascaded multilevel inverter. The basic asymmetrical hybrid circuit is described and is capable of generating 17 voltage levels. The various modes of deriving 17 levels are explained and the proposed topology is compared with existing topologies in various aspects. Neural network controller can be used to generate the gating pulses. The algorithm can be trained online by using back propagation algorithm and also an algorithm to determine the number of levels, maximum voltage ratings and power loss is explained. The simulation can be done by MATLAB Simulink.